Progress of research and application of Heyndrickxia coagulans (Bacillus coagulans) as probiotic bacteria - Liang, Jie; Li, Chunhai; Chen, Zouquan; Guo, Fangyu; Dou, Jiaxin; Wang, Ting; Xu, Zhen Shang (Frontiers in Cellular and Infection Microbiology, 2024)
Probiotics are defined as living or dead bacteria and their byproducts that maintain the balance of the intestinal microbiome. They are non-toxic, non-pathogenic, and do not release any toxins either within or outside the body. Adequate consumption of probiotics can enhance metabolite production, increase immunity, maintain a balanced intestinal flora, and stimulate growth. Probiotics do not have negative antibiotic effects and help maintain the natural flora in animals in a balanced state or prevent dysbacteriosis. Heyndrickxia coagulans (H. coagulans) is a novel probiotic species that is gradually being used for the improvement of human health. Compared to commonly used probiotic lactic acid bacteria, H. coagulans can produce spores, which provide the species with high resistance to adverse conditions. Even though they are transient residents of the gut, beneficial bacteria can have a significant impact on the microbiota because they can outnumber harmful germs, and vice versa. This article discusses the probiotic mechanisms of H. coagulans and outlines the requirements for a substance to be classified as a probiotic. It also addresses how to assess strains that have recently been discovered to possess probiotic properties.